Conflict in Schools: How Effective Communication Can Address Bullying Problems in Educational Institutions - Mannan, Ahmad Faidul; Shulhani, Rahmat; Baharun, Hasan (Transformation of Islamic Management and Education, 2024)
This study aims to identify the factors influencing communication among stakeholders and to explore communication strategies that can be implemented to address bullying issues at Nurul Jadid Junior High School. Employing a qualitative approach with a case study method, data were collected through direct observation, in-depth interviews with students, teachers, and parents, as well as documentation of school policies and bullying incident reports. Data analysis was conducted descriptively through data reduction, data presentation, and conclusion drawing. The findings indicate that bullying at Nurul Jadid Junior High School is predominantly verbal (45%), followed by physical bullying (35%) and social bullying (20%). A culture of seniority and weak supervision are the primary contributing factors to bullying behavior. This study highlights the need for value-based anti-bullying programs grounded in Islamic principles, the strengthening of supervision systems, and the implementation of secure and anonymous reporting mechanisms to encourage students to report bullying cases without fear. By applying effective communication strategies, the school can create a safer and more harmonious learning environment while supporting the positive character development of students.